2001
DOI: 10.1063/1.1401089
|View full text |Cite
|
Sign up to set email alerts
|

Bulk synthesis of silicon nanowires using a low-temperature vapor–liquid–solid method

Abstract: Silicon nanowires will find applications in nanoscale electronics and optoelectronics both as active and passive components. Here, we demonstrate a low-temperature vapor-liquid-solid synthesis method that uses liquid-metal solvents with low solubility for silicon and other elemental semiconductor materials. This method eliminates the usual requirement of quantum-sized droplets in order to obtain quantum-scale one-dimensional structures. Specifically, we synthesized silicon nanowires with uniform diameters dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
190
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(199 citation statements)
references
References 25 publications
4
190
0
2
Order By: Relevance
“…1 Earlier, we showed that Si nanowire growth using lowmelting metal droplets is not limited by the cluster size and occurs at a high density from a single droplet. 2 Later, this concept has been used for demonstrating the synthesis of several materials systems such as Si, Bi, amorphous SiO 2 , and Si x N y H nanowires. 3 In particular, the direct synthesis of nanowires of compounds of low-melting metals such as Group III-nitrides, sulfides, oxides, and so forth 4 under metal-rich conditions fall under this concept as well.…”
Section: Introductionmentioning
confidence: 99%
“…1 Earlier, we showed that Si nanowire growth using lowmelting metal droplets is not limited by the cluster size and occurs at a high density from a single droplet. 2 Later, this concept has been used for demonstrating the synthesis of several materials systems such as Si, Bi, amorphous SiO 2 , and Si x N y H nanowires. 3 In particular, the direct synthesis of nanowires of compounds of low-melting metals such as Group III-nitrides, sulfides, oxides, and so forth 4 under metal-rich conditions fall under this concept as well.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the growth of AlN on sapphire substrates, the growth of high-structural-quality AlN on Si substrates is extremely difficult owing to temperature limitation of the process and the formation of Al-Si. (10) It is well established that in order to improve the structural quality of AlN, high-temperature growth must be employed owing to the inherent lack of lateral movement of aluminum species and the high sticking coefficient of Al of close to unity. (1,17,18) Because of its high sticking coefficient close to unity, aluminum tends to form only islands of AlN during growth after the reaction with NH 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Unlike sapphire, GaN cannot be grown directly on Si owing to the formation of eutectic Ga-Si and the associated meltback etching of Si substrates. (10) This necessitates the use of AlN as a starting mask material to facilitate the subsequent growth of group-III-nitride-based structures on Si substrates. When the growth is started with an AlN nucleation layer, it is difficult to grow thick GaN with the high structural quality required for device structures directly on top of the AlN without cracks, particularly when large substrates are used.…”
Section: Introductionmentioning
confidence: 99%
“…The 1D nanostructure has been synthesized by various methods, such as conventional chemical vapor deposition (CVD), laser ablation, solutions, oxide-assisted and template-assisted method [3,4,5,6]. It has been generally grown using metal-catalyzed vapor-liquid-solid (VLS) mechanism [7,8]. In particular, silicon nanowires (SiNWs) are fascinating materials due to the fundamental function of the semiconductor industry, and their characteristics are well studied.…”
Section: Introductionmentioning
confidence: 99%